2004
DOI: 10.1177/13670069040080040301
|View full text |Cite
|
Sign up to set email alerts
|

The development of narrative competence in the L1 and L2 of Spanish-English bilingual children

Abstract: The present paper examines the development of narrative competence in the two languages of three Spanish-English bilingual children with different proficiency levels in each language. The children's narratives, elicited at two different times over a six-month span, are examined in terms of the young narrator's ability to organize the story around an overall theme line, his/her capacity to evaluate the narrative and reach the audience, and his /her appropriate use of those linguistic devices—such as temporal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 7 publications
6
37
1
9
Order By: Relevance
“…Psychological relations between internal reactions and their precipitating events seemed more resistant to the effects of language background or age, as corroborated by their quite pervasive expression in L1 and L2 at both ages. Together, these findings are not in line with previous studies on the development of evaluation in picture-based narratives (as a partially similar category to psychological reactions, see footnote 4), where the overall proportion of evaluative devices was reported to be scarce at these developmental stages (Bamberg & Damrad-Frye, 1991;Bavin, 2009;Nakamura, 2009;Pearson, 2001). We believe that perceptual saliency represented in facial expressions and body gestures throughout the pictures triggered the consistent expression of psychological causation, where narrators mostly referred to the emotional reactions of the protagonists.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Psychological relations between internal reactions and their precipitating events seemed more resistant to the effects of language background or age, as corroborated by their quite pervasive expression in L1 and L2 at both ages. Together, these findings are not in line with previous studies on the development of evaluation in picture-based narratives (as a partially similar category to psychological reactions, see footnote 4), where the overall proportion of evaluative devices was reported to be scarce at these developmental stages (Bamberg & Damrad-Frye, 1991;Bavin, 2009;Nakamura, 2009;Pearson, 2001). We believe that perceptual saliency represented in facial expressions and body gestures throughout the pictures triggered the consistent expression of psychological causation, where narrators mostly referred to the emotional reactions of the protagonists.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies of story comprehension have found that enablement is a weaker relation as compared to others (Trabasso et al, 1989;Tapiero, van den Broek, & Quintana, 2002), a claim that is worth examining in the development of narrative production. From these findings, one may suggest a gradual progression from locally to more globally driven expression of causal relations in L1 and L2, although some types of causality relations may be predominantly data-driven and thus more reliant on accessible language forms (Karmiloff-Smith, 1985;Nakamura, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At age 5, children produce more complete stories in L1 than in L2 according to Montanari (2004). And finally, at ages 8 and 9, most children reproduce the complete narrative structure in their L1, according to data presented by Berman andSlobin (1994) andDe Weck (1991).…”
Section: Elements Analysedmentioning
confidence: 89%
“…Einschränkend ist allerdings zu sagen, dass unsere Ergebnisse zum selbstgesteuerten Lesen nicht mit den gleichen Kindern gewonnen wurden wie die in den Studien von Kupersmitt/Yifat/Blum-Kulka (2014) und Montanari (2004). Die Studien unterscheiden sich im Alter der Kinder, in den beteiligten Sprachen und in der Modalität (schriftlich vs. mündlich).…”
Section: Introductionunclassified